The city as a poetic argument: anagnorisis and map of illusions in Columbus (Kogonada, 2017) - Rubio de Olazabal, Juan (Street Art & Urban Creativity, 2024)
The film Columbus (Kogonada, 2017) poses a mirror relationship between the inner dynamism of the characters and the dynamism of the city. The latter is deployed in two senses: the cartography or tour of the city itself, that is, Columbus (Indiana, USA) that gives the film its title, and the architectural design of its buildings. This dramatic-cartographic-architectural triangle turns the work into a pertinent case study to understand the catalytic possibilities of the city in the discovery of personal identity and, in turn, to delve into the cinema-urban synergies. The link or ideal meeting between these two arts appears here as movement: the psychological-moral of the characters and the sculpture in museums, churches, squares, etc. that make up the city. Starting from a methodology based on the psychological notions of Aristotelian poetics (anagnorisis, catharsis) and the anthropological notions of Julián Marías about the projection of desire as a map of illusions (Marías, 2018), we propose a poetic analysis of the city of Columbus "Mecca" of architectural modernism in the USA - as a device to rehearse the happiness of the characters, mainly their possibilities of (self) recognition. To our critical apparatus we incorporate notions of audiovisual analysis (typology and shot composition) with support in architectural terminology on urban representation in cinema (Deltell and García, 2022). A concern, the latter, even prior to the filming of Columbus and that contributes to reinforcing the relevance of our proposal.